Reversals in past long-term trends in educational inequalities in life expectancy for selected European countries - Zazueta-Borboa, JD; Martikainen, P; Aburto, JM; Costa, G; Peltonen, R; Zengarini, N; Sizer, A; Kunst, AE; Janssen, F (BMJ Publishing Group, 2023)
Background Across Europe, socioeconomic inequalities in mortality are large and persistent. To better understand the drivers of past trends in socioeconomic mortality inequalities, we identified phases and potential reversals in long-term trends in educational inequalities in remaining life expectancy at age 30 (e30), and assessed the contributions of mortality changes among the low-educated and the high-educated at different ages.